Ligand field model for bent (C(2v))d1 metallocene complexes - Pavlík, Ivan; Fiedler, Josef; Vinklárek, Jaromír; Pavlišta, Martin (Univerzita Pardubice, 2000)
Ligand field calculations, excluding spin-orbit soupling, have been carried out for bent d1 metallocene complexes in C2v symmetry. The application of the results to the interpretation of the d-d electronic spectrum of the representative d1 complex vanadocene dichloride is discussed with particular reference to the relative energy of the five d orbitals.
Keywords: ligandy; nelineární systémy; Metalloceny; komplexy; molekulární orbitaly; modely